2017
DOI: 10.1080/13621718.2017.1341463
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel Fe–Mn–Ni cryogenic steel: microstructure-property relationship during simulated welding

Abstract: We describe here the microstructural evolution during simulation of welding thermal cycles in novel Fe-Mn-Ni cryogenic steel and elucidate the mechanism of cryogenic toughness. The original microstructure was tempered martensite and ∼ 10% retained austenite. Electron backscattered diffraction indicated that the frequency of large-angle boundaries with misorientation > 15°was similar at peak temperatures of 1320, 870 and 760°C. The volume fraction of retained austenite determined by X-ray diffraction was ∼ 11% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…As the Mn content increased, a twinning-induced mechanism became apparent, which enhanced the low-temperature toughness of the 24Mn and 26Mn steels in comparison to the 22Mn steel. Sohn et al [90] investigated the mechanical properties of four high-manganese steels, Fe- (19,22) Mn and Fe- (19,22) Mn-2Al, at both room and low temperatures. Their findings indicated that with a decrease in the testing temperature, the impact absorption energy of the 19Mn and 22Mn steels diminished significantly.…”
Section: Mnmentioning
confidence: 99%
See 2 more Smart Citations
“…As the Mn content increased, a twinning-induced mechanism became apparent, which enhanced the low-temperature toughness of the 24Mn and 26Mn steels in comparison to the 22Mn steel. Sohn et al [90] investigated the mechanical properties of four high-manganese steels, Fe- (19,22) Mn and Fe- (19,22) Mn-2Al, at both room and low temperatures. Their findings indicated that with a decrease in the testing temperature, the impact absorption energy of the 19Mn and 22Mn steels diminished significantly.…”
Section: Mnmentioning
confidence: 99%
“…Thanks to its face-centered cubic (FCC) crystal structure, high-manganese steel maintains its ductility without undergoing a ductile-to-brittle transition across a broad temperature spectrum, from room temperature (RT) down to liquid nitrogen temperature (LNT, −196 • C) [18,19]. This inherent characteristic ensures the material's cryogenic toughness to a considerable degree.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, novel cryogenic high-Mn austenitic steels have been developed with their excellent cryogenic toughness and remarkable economic advantages for replacing traditional 9% nickel cryogenic steels, austenitic stainless steels and invar alloys for the manufacture of liquefied natural gas (LNG) tanks [1,2]. The high-Mn cryogenic steel in the fabrication of LNG tanks should be connected by welding, and submerged arc welding is one of the most widely used welding methods in high-Mn cryogenic steel [3].…”
Section: Introductionmentioning
confidence: 99%